2015
DOI: 10.1155/2015/154239
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Degradation of Lactide-co-Glycolide Polymer with Basic Nucleophilic Drugs

Abstract: The purpose of this study was to examine the degradative effect of weakly basic nucleophilic drugs on a lactide-co-glycolide (PLGA) polymer in a microsphere formulation. Biodegradable PLGA microspheres of two second-generation atypical antipsychotics, Risperidone and Olanzapine, were manufactured using a solvent extraction/evaporation technique. The effect of drug content, buffer pH and temperature on polymer molecular weight and degradation, were examined via a series of experiments and compared against a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…In the current study, it is likely that the delayed hydration process of ester end-capped PLGAs [43] influenced the rate of polymer hydration in vitro and subsequently facilitated the release of ketamine out of the microparticles. This is in agreement with the findings by others that the encapsulation of weakly basic drugs into PLGA can accelerate the biodegradation of PLGA [44,45]. Additionally, the acids may also produce local lowering of the pH [35] to accelerate ketamine release.…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, it is likely that the delayed hydration process of ester end-capped PLGAs [43] influenced the rate of polymer hydration in vitro and subsequently facilitated the release of ketamine out of the microparticles. This is in agreement with the findings by others that the encapsulation of weakly basic drugs into PLGA can accelerate the biodegradation of PLGA [44,45]. Additionally, the acids may also produce local lowering of the pH [35] to accelerate ketamine release.…”
Section: Discussionsupporting
confidence: 92%
“…For basic drugs, however, there are conflicting views of the impact on degradation. One viewpoint is that degradation will be accelerated; basic drugs, such as tertiary amine or nucleophilic drugs, catalyze the matrix degradation that will accelerate the release rate because of a bulk erosion of the matrix . An opposite viewpoint is that drug release can be suppressed; basic drugs can neutralize the generating acid from polymer hydrolysis so as to minimize the autocatalytic effect, thereby leading to a slower degradation rate and consequent reduced drug release rates …”
Section: Materials Factors (Materials Properties)mentioning
confidence: 99%
“…One viewpoint is that degradation will be accelerated; basic drugs, such as tertiary amine or nucleophilic drugs, catalyze the matrix degradation that will accelerate the release rate because of a bulk erosion of the matrix. 17,76,77 An opposite viewpoint is that drug release can be suppressed; basic drugs can neutralize the generating acid from polymer hydrolysis so as to minimize the autocatalytic effect, thereby leading to a slower degradation rate and consequent reduced drug release rates. 43,78,79 As an example of the studies to address the impact of drug-polymer interaction on the release behavior, Klose et al 34 reported in vitro release behaviors of lidocaine and ibuprofen drugs from PLGA-based polymers at pH 7.4 as Complete drug release in 20 days shown in Table V.…”
Section: Drugsmentioning
confidence: 99%
“… Drug name, IUPAC name, and structure Dosage Physiochemical properties Mol.wt. Log P pKa Solubility (H 2 O) Olanzapine 2-methyl-4-(4-methylpiperazin-1-yl)-10H-thieno [2,3b] [1,5]benzodiazepine Target: 10 mg/day 312 g/mol 2 7.37 a 0.039 mg/ml Risperidone 3- [2- [4-(6-fluoro-1,2-benzoxazol-3-yl) piperidin-1-yl]ethyl]-2-methyl-6,7,8,9-tetrahydro-pyrido [1,2-a]pyrimidin-4-one Range: 2–10 mg/day 410 g/mol 3.49 8.24 a 0.064 mg/ml b Log P: partition co-efficient; a [18] ; b [19] …”
Section: Introductionmentioning
confidence: 99%